The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/s19225010
|View full text |Cite
|
Sign up to set email alerts
|

Standard Analytical Methods, Sensory Evaluation, NIRS and Electronic Tongue for Sensing Taste Attributes of Different Melon Varieties

Abstract: Grafting by vegetables is a practice with many benefits, but also with some unknown influences on the chemical composition of the fruits. Our goal was to assess the effects of grafting and storage on the extracted juice of four orange-fleshed Cantaloupe type (Celestial, Donatello, Centro, Jannet) melons and two green-fleshed Galia types (Aikido, London), using sensory profile analysis and analytical instruments: An electronic tongue (E-tongue) and near-infrared spectroscopy (NIRS). Both instruments are known f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…As well as distinguishing elderberry genotypes based on fruit quality [ 10 ]. NIR spectroscopy is a very powerful tool for analysis of fruits and vegetables and related food products [ 11 , 12 ]. Our study is the first that describes a NIR spectroscopy technique for the determination of TAC in elderberry.…”
Section: Introductionmentioning
confidence: 99%
“…As well as distinguishing elderberry genotypes based on fruit quality [ 10 ]. NIR spectroscopy is a very powerful tool for analysis of fruits and vegetables and related food products [ 11 , 12 ]. Our study is the first that describes a NIR spectroscopy technique for the determination of TAC in elderberry.…”
Section: Introductionmentioning
confidence: 99%
“…Grieneisen et al [15] conducted a review of 202 different rootstocks and 1023 experimental treatments related to tomato grafting, and they concluded that fruit quality data based on sensory tests were rare among the published studies. Sensory evaluation of grafted plants of the members of the Cucurbitaceae family, i.e., melon [16], watermelon [17,18], and cucumber [19], and those of the Solanaceae family [20,21] have been conducted, but there is relatively few data for eggplant.…”
Section: Introductionmentioning
confidence: 99%
“…This substantiates the importance of NIR spectroscopy for rapid monitoring of additives and preservatives in fruit juices when either transmittance, reflectance, or diffuse-reflectance mode is used. In combination with standard analytical techniques, both a benchtop and handheld SMC NIR in reflectance mode could discriminate different varieties of green and orange fleshed melons with 100% classification accuracy in LDA and predict multiple sensory parameters in PLS regression with high precision (R 2 up to 0.96) and low errors (RMSECV as low as 0.24 g/mL) after cross-validation [ 80 ]. Transmittance mode benchtop FT-NIR provided high R 2 in cross-validation (up to 0.94) and low errors (RMSECV as low as 5.07 mg nitrogen/L) when it was used to measure total yeast assimilable nitrogen, free amino nitrogen, and ammonia in 900 grape juice samples from 28 cultivars over three seasons [ 81 ].…”
Section: Near Infrared (Nir) Spectroscopy: Historical Background Amentioning
confidence: 99%
“…The same potentiometric E-tongue measurements combined with LDA showed 100% separation between the flesh of different colors. Good correlations were found between some standard analytical parameters and E-tongue sensor signals with PLS regression models [ 80 ].…”
Section: Electronic Tongue: Historical Background and Food Qualitymentioning
confidence: 99%